Neuropharmacological and gastrointestinal evaluation of coloring agent metanil yellow used in food and beverages (Jahangirnagar University Journal of Biological Sciences, 2019)
Metanil yellow as a coloring agent is widely used in food industry to make food more appealing, appetizing and informative. Regulatory organization like FDA maintains strict rules but in our country coloring agents are at randomly used. This study is designed to evaluate side effects of metanil yellow on central nervous system and gastrointestinal tract in mice. Open field, hole board and hole cross tests were done to evaluate the effects of central nervous system; while castor oil and magnesium sulfate induced diarrheal tests were done to observe the effects on gastrointestinal tract. The mice were administered a dose of 5 gm/kg body weight of metanil yellow considered as 1x dose (MTYx) and another dose of 20 gm/kg body weight of metanil yellow considered as 4x dose (MTY4x). In the study, the metanil yellow exhibited central nervous system stimulatory effects based on hole cross test (p=000***, p=.003**, p=000***, p=.001***), hole board test (p=.03*, p=.005**, p=.041*, p=0.018*), and open field test (p=0.004**, p=.002**, p=.002**, p=.011*, p=0.008*). On the other hand gastrointestinal test results failed to show a significant effect (p=.04*).Jahangirnagar University J. Biol. Sci. 8(1): 35-44, 2019 (June)